Analysis of the Use of Generators and Rectifier Regulators as Additional Charging Systems for BLDC-Based Electric Bicycles - Pratiwi, Nurul Dwi; Muhammad, Rahmadis; Fiatno, Aris (Journal of Engineering Science and Technology Management (JES-TM), 2023)
The development of technology and mobility has encouraged humans to innovate and create environmentally friendly means of transportation and can reduce dependence on fuel oil which will eventually run out. Currently, transportation equipment using electrical energy is starting to appear as an alternative energy source, including electric bicycles. In this research, electric bicycles were produced equipped with generators and rectifiers to produce additional electrical energy. The generators utilizes the rotation of the front wheels to produce electrical energy which is then channeled through the rectifier and stored in the battery. This research aims to determine the benefits of using generators and rectifiers as additional charging systems for BLDC-based electric bicycles by conducting direct road test of electric bicycles. The result show that the use of a generator and rectifier can increase the distance traveled by up to 2 km. An electric bicycle with a capacity of 24V x 14 Ah can over a distance of 13 km without a generator and 15 km with a generator.